Frontal system changes in the Southeastern Atlantic Ocean - Braga, Martim Mas e (2017)
The transition between the South Atlantic and the Southern Ocean is marked by a frontal system that includes both the South Atlantic Current and the Antarctic Circumpolar Current (ACC). In the eastern part of the basin the latitudinal position of the fronts that compose this system is thought to control the input of warm waters into the Atlantic basin through the Agulhas Leakage. Changes in the Subtropical and Polar regimes associated with the system that marks the boundary between the Subtropical Gyre and the ACC are investigated using the simulation results of the ocean component of the National Center for Atmospheric Research (NCAR) Community Earth System Model (CESM), POP2. Sea surface height gradients and specific contours are used to identify and track the ocean fronts position. We compare the Subtropical Front position at the eastern edge of the South Atlantic to changes in temperature and salinity, as well as Agulhas Current transports and the overlying wind field, in order to determine what could be driving frontal variability at this region and its consequences to volume transport from the Indian into the Atlantic. Results suggest that the Subtropical Front is not the southern boundary of the subtropical gyre, but it responds to changes in the \"Supergyre\", especially the Indian Ocean Subtropical Gyre expansion.